2022
DOI: 10.33795/ijfte.v1i01.221
|View full text |Cite
|
Sign up to set email alerts
|

Mixture of Faults Identification on Power Transformers Using Multi-Method Dissolved Gas Analysis

Abstract: Utilities rely on the various Dissolved Gas Analysis (DGA) interpretation methods to identify incipient fault within power transformers. However, confusion often arises due to the use of different DGA methods which can have different results or fail to detect mixture of faults (multiple faults). This paper implements the combination of Duval Triangle and Duval Pentagon as one of the most consistent methods to do fault identification based on DGA. Recent historical DGA data of generator step up high voltage pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The findings of this study revealed a hard correlation between coefficients parameter and the transformer's total operating time, which may impact its lifespan. Another study [14] not only assesses the condition of power transformers but also detects power disturbances using DGA data and a combination of Duval Methods, in line with the IEEE C57.104-(2019) guidelines. Additionally, other studies [15], [16], [17] discuss the identification of faults in transformer oil insulation through DGA analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of this study revealed a hard correlation between coefficients parameter and the transformer's total operating time, which may impact its lifespan. Another study [14] not only assesses the condition of power transformers but also detects power disturbances using DGA data and a combination of Duval Methods, in line with the IEEE C57.104-(2019) guidelines. Additionally, other studies [15], [16], [17] discuss the identification of faults in transformer oil insulation through DGA analysis.…”
Section: Introductionmentioning
confidence: 99%
“…After analyzing the transformer oil's status, the faults can be identified [21]. Previous studies have commonly used methods such as the IRM (IEC Ratio Method), RRM (Roger's Ratio Method), DRM (Doernenburg Ratio Method), DTM (Duval Triangle Method), and DPM (Duval Pentagon Method) [14]. This case study will compare the interpretation result using two different standards, namely IEC 60599-(2015) and IEEE C57.104-(2019) to determine effectiveness in determining conditions in a transformer using DGA.…”
Section: Introductionmentioning
confidence: 99%